Pola Makan Remaja Putri Terhadap Kejadian Anemia di SMAN 3 Tuban - Wardhani, Salsabiela Bunga; P, Teresia Retna; Wahyurianto, Yasin (Peneliti.net, 2024)
For adolescents, food is a basic need for the growth and development of their bodies. Lack of food consumption, both qualitatively and quantitatively will cause the body's metabolic processes to occur, so that in consuming food, what needs to be considered is balanced nutrition. The cause of anemia in adolescents is due to irregular eating patterns. Adolescents with anemia in Tuban Regency in 2018 were 463 people. An initial survey by researchers at SMAN 3 Tuban found that 9 out of 10 children had signs of anemia. The aim of the study was to determine the relationship between the eating habits of young women and the incidence of anemia at SMAN 3 Tuban Correlation analytic research design, cross-sectional approach. The population of this study is all young girls at SMAN 3 Tuban class XI for the 2022 academic year, 152 students, a sample of 110 students. The sampling technique is simple random sampling. Independent variable eating pattern of young women, dependent variable the incidence of anemia. data collection distributed questionnaires and observed signs of anemia symptoms. processing data using chi-square test. The results of the study were that most (75%) of female adolescents had a poor diet, almost half (42.7%) of adolescents experienced anemia. Chi-square test results p = 0.001 <0.05. These results indicate that there is a relationship between the diet of young women and the incidence of anemia. The better the diet of female adolescents, the lower the risk of these adolescents experiencing anemia. Efforts that can be made by the school are to carry out activities to check Hb levels for young girls at least once every 6 months carried out thoroughly, schools carry out the habit of taking iron tablets together at school once a month accompanied by a counseling teacher.